The Diplomacy of Displacement: Nigeria's Foreign Policy and the Governance of Internal Migration in the Lake Chad Basin, 2014–2025 - Obaji-Akpet Immaculata Ofu; Owa Egbara Owa (Universitas Negeri Makassar, 2026)
The Boko Haram insurgency and its regional consequences have generated one of the world's most severe displacement crises, with over 2.5 million people displaced across Nigeria, Niger, Chad, and Cameroon. While the humanitarian dimensions of this crisis have received considerable scholarly and policy attention, the diplomatic dimensions remain significantly underexplored. This paper examines how Nigerian foreign policy has addressed the governance of cross-border displacement in the Lake Chad basin from 2014 to 2025. It argues that Nigeria has pursued a dual and often contradictory strategy of securitisation and regional cooperation. On one hand, Nigerian policymakers have framed displacement primarily as a security threat, justifying military responses and border controls. On the other hand, Nigeria has engaged in multilateral diplomacy through the Lake Chad Basin Commission and the Multinational Joint Task Force, recognising that displacement cannot be managed unilaterally. The paper analyses the tensions between these two approaches, the implications for the protection of displaced persons, and the lessons for understanding how states in the global South navigate the intersection of security, migration, and diplomacy. Drawing on securitisation theory and the emerging literature on migration diplomacy, the study contributes to the growing field of research on the foreign policy dimensions of internal displacement and offers policy recommendations for a more coherent Nigerian approach to regional displacement governance.